“Above the Sceptred Sway”: Retrieving the Quality of Mercy - William F. Ransome (Crítica)
Mercy is often thought to be a praiseworthy moral virtue. However, the quality of mercy has been thrown into doubt. Since to be merciful is to be lenient to a wrongdoer beyond the dictates of justice, it seems as if mercy cannot be a praiseworthy virtue. I argue that several recent attempts to reconcile mercy with justice fail, and that the subsequent endeavour to resurrect mercy as a praiseworthy moral virtue is doubtful. However, I also show how the praiseworthy quality of mercy can be retrieved, if we carefully reconstruct the moral case in its favour outside the law.